4-(10-Phenyl-9-Anthracenyl)-1,2-Benzenediol - Nicola Edwards; Kelsey Harris (Molbank)
The title compound, 4-(10-phenyl-9-anthracenyl)-1,2-benzenediol, was synthesized using a two-step protocol. In the first step, 9-phenyl,10-bromoanthracene was coupled to 3,4-dimethoyphenylboronic acid by employing Pd(PPh3)4 as the catalyst and potassium carbonate as the base. Methoxy group removal was effected using HBr in the presence of acetic acid in the second step. Overall, two novel 9,10-diphenylanthracence-based compounds were synthesized in this work; standard spectroscopic techniques and high-resolution mass spectrometry were employed in their characterization. The photophysical properties of these compounds are also reported. These compounds are potentially useful as sensors, catalysts and building blocks for larger architectures.